Study of Actuarial Characteristics of One-Year and Ultimate Reserve Risk Distributions Based on Market Data - Szatkowski, Marcin (Central European Journal of Economic Modelling and Econometrics, 2022)
In this work, we perform an analysis of the characteristics of the one-year and ultimate reserve risk distributions commonly used in actuarial science: duration, first development factor, coefficient of variation, skewness coefficient, skewnessto-CoV ratio, emergence factor, emergence pattern, and risk margin run-off patterns. Our study is based on empirical data for two European markets: the Polish and Slovak markets. We provide benchmarks and ranges for the considered characteristics, as well as analyse the relations between them. We study Solvency II lines of business and compare our coefficients of variation to the Standard Formula reserve risk standard deviations. We investigate more deeply the topic of emergence pattern and risk margin run-off patterns.